Synthesis and physical-chemical properties of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives and their evaluation for antimicrobial and diuretic activities - Aleksandrova, K. V.; Mykhalchenko, Ye. K.; Shkoda, O. S.; Vasyliev, D. A.; Александрова, Катерина Вячеславівна; Михальченко, Євген Костянтинович; Шкода, Олександр Станіславович; Васильєв, Денис Андрійович; Александрова, Е. В.; Михальченко, Е. К.; Шкода, А. С.; Васильев, Д. А. (Запорізький державний медичний університет, 2021)
One of the most important tasks of our indigenous pharmaceutical science is the necessity for new medicines because existing drugs are characterized by various side effects, resistance, high toxicity, and so on. New bioactive molecule synthesis utilizes substances of natural origin as well as chemically modified ones. Thus, the researcher’s attention is mainly focused on 3-,7-,8-substituted derivatives of the natural heterocyclic xanthine system, which possess a wide range of pharmacological action. Synthesis of a novel of (3-benzyl-8- propylxanthin-7-yl)acetohydrazides with antimicrobial and diuretic activities described in the paper. The aim of this work is to develop efficient methods for synthesis of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives, and to study their physical-chemical properties. Materials and methods. Two-hour boiling of propyl 2-(3-benzyl-8-propylxanthine-7-yl)acetate by excess hydrazine hydrate in propan-2-ol medium have yielded the key the key intermediate 2-(3-benzyl-8-propylxanthine-7-yl)acetohydrazide. Further transformation of the latter has led to formation of corresponding acetohydrazide derivatives achieved by the reaction with aliphatic, aromatic, heterocyclic aldehydes, and ketones. The structure and the relative configuration of the synthesized compounds were elucidated by analyzing their physical-chemical data. Results. The synthesis and optimization of reaction conditions of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives were conducted. The identification of all synthesized compounds was aided by various physical-chemical methods (thin layer chromatography, elemental analysis, IR, and 1H NMR spectroscopy). Conclusions. As a result of synthetic research the preparative synthesis method of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives possessing antimicrobic, and diuretic activities was developed. Створення нових лікарських препаратів – одне з найважливіших завдань вітчизняної фармацевтичної науки. Це зумовлено наявні- стю у препаратів небажаних побічних ефектів, набуттям резистентності, високою токсичністю тощо. Для створення біоактивних молекул застосовують і речовини природного походження, і нові синтезовані сполуки та продукти їхньої хімічної модифікації. У цьому аспекті увагу дослідників привертають 3-,7-,8-заміщені похідні природної гетероциклічної системи ксантину, що мають широкий спектр фармакологічної дії. Наведено синтез неописаних у фаховій літературі іліденгідразидів 3-бензил-8-пропілксантин-7-іл ацетатної кислоти, які характеризуються протимікробними та діуретичними властивостями. Мета роботи – розроблення методів одержання іліденпохідних 3-бензил-8-пропілксантиніл-7-ацетатної кислоти та вивчення фізико-хімічних властивостей цих сполук. Матеріали та методи. Як вихідну сполуку використали гідразид 3-бензил-8-пропілксантиніл-7-ацетатної кислоти, одержаний раніше двогодинним кип’ятінням н-пропілового естеру 3-бензил-8-пропілксантиніл-7-ацетатної кислоти з надлишком гідразин гідрату в середовищі пропан-2-олу. Надалі вивчили реакцію гідразиду 3-бензил-8-пропілксантиніл-7-ацетатної кислоти з аліфатичними, ароматичними, гетероциклічними альдегідами та кетонами, в результаті отримали відповідні іліденпохідні. Будова та індивідуальність синтезованих сполук підтверджена комплексом фізико-хімічних досліджень. Результати. Здійснили синтез і визначили оптимальні умови перебігу реакцій одержання іліденпохідних 3-бензил-8-пропілксантиніл-7-ацетатної кислоти. За допомогою фізико-хімічних методів дослідження (хроматографія в тонкому шарі сорбенту, елементний аналіз, ІЧ- та 1Н ЯМР-спектроскопія) встановили структуру та індивідуальність нових синтезованих сполук. Висновки. У результаті синтетичного дослідження опрацювали препаративну методику синтезу іліденгідразидів 3-бензил-8-пропілксантиніл-7-ацетатної кислоти, які мають протимікробні та діуретичні властивості. наличием у существующих препаратов нежелательных побочных эффектов, приобретением резистентности, высокой токсичностью и т. д. Для создания биоактивных молекул применяются и вещества природного происхождения, и новосинтезированные соединения и продукты их химической модификации. В этом плане внимание исследователей привлекают 3,7,8-замещенные производные природной гетероциклической системы ксантина, проявляющие широкий спектр фармакологической активности. Представлен синтез неописанных в специализированной литературе илиденгидразидов 3-бензил-8-пропилксантинил-7-ацетатной кислоты, которые проявляют противомикробную и диуретическую активности. Цель работы – разработка методов получения илиденпроизводных 3-бензил-8-пропилксантинил-7-ацетатной кислоты и изучение физико-химических свойств этих соединений. Материалы и методы. В качестве исходного соединения использован гидразид 3-бензил-8-пропилксантинил-7-ацетатной кислоты, полученный ранее двухчасовым кипячением н-пропилового эфира 3-бензил-8-пропилксантинил-7-ацетатной кислоты с избытком гидразингидрата в среде пропанола-2. В дальнейшем изучена реакция гидразида 3-бензил-8-пропилксантинил-7-ацетатной кислоты с алифатическими, ароматическими, гетероциклическими альдегидами и кетонами, в результате которой получены соответствующие илиденпроизводные. Строение и индивидуальность синтезированных соединений подтверждена комплексом физико-химических исследований. Результаты. Осуществлен синтез и определены оптимальные условия протекания реакций получения илиденпроизводных 3-бензил-8-пропилксантинил-7-ацетатной кислоты. С помощью физико-химических методов исследования (хроматография в тонком слое сорбента, элементный анализ, ИК и 1Н ЯМР-спектроскопия) установлены структура и индивидуальность новосинтезированных соединений. Выводы. В результате синтетического исследования разработана препаративная методика синтеза илиденгидразидов 3-бензил-8-пропилксантинил-7-ацетатной кислоты, которые проявляют противомикробную и диуретическую активности.
Синтез і фізико-хімічні властивості іліденпохідних гідразиду 3-бензил-8-пропілксантиніл-7-ацетатної кислоти, що мають протимікробні та діуретичні властивості
Синтез и физико-химические свойства илиденпроизводных гидразида 3-бензил-8-пропилксантинил-7-ацетатной кислоты, которые проявляют противомикробные и диуретические свойства
Александрова К. В. - ORCID ID: 0000-0003-4436-4036; Михальченко Є. К. - ORCID ID: 0000-0002-6388-2966; Шкода О. С. - ORCID ID: 0000-0002-5678-2801; Васильєв Д. А., - ORCID ID: 0000-0002-9671-1397.
Keywords: 3-benzylxanthine; acetohydrazide; physicochemical properties; 3-бензилксантин; іліденгідразиди; фізико-хімічні властивості; илиденгидразиды; физико-химические свойства